Fostering Leadership and Gender Equity Through Student Groups: A Case Study in Engineering Education - Ruiz-Cantisani, M. Ileana; Lara-Prieto, Vianney; Romero-Robles, Laura E.; Burgos-Lopez, María Yolanda; Lopez-Caudana, Edgar Omar; Membrillo-Hernánez, Jorge (LACCEI, 2025)
One of the challenges of higher education is to achieve gender equity in the areas of Science, Technology, Engineering and Mathematics (STEM), from enrollment, retention to graduation. Universities develop different actions to impact this challenge, through strategies, policies, and initiatives, all conducted by their professors, leaders and students. This research has a qualitative approach, which aims to present a case study at a School of Engineering, that has as a strategic initiative to increase the percentage of women in STEM areas. The research focuses on the involvement of students in promoting the strengthening of this gender equity initiative through student groups, analyzing: the approach of the university in relation to student groups and gender equity as a context, analysis of the academic programs that integrate it with its students by gender, the purposes of each student group linked to these initiatives in STEM area and the opinion of candidates for graduation in relation to the activities of student groups. The results show that student groups focused on equity aim to create a supportive and empowering environment through various activities. Despite positive evaluations from graduating students, there are still gender participation gaps in engineering fields. Both the institution and the engineering school should enhance initiatives to meet the common goals of these groups.